Analysis Influence: Learning True False Learning Model Based Domino Cards on Student Learning Outcomes - Sunia, Siti (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the learning outcomes of students using and not using the True or False learning strategy based on domino cards on the reproductive system material in class XI science at Public High School 8 Bandar Lampung. Methodology: This type of research is a quasi-experimental research with a Pretest-Posttest Control Group Design research design. The sampling technique in this study was purposive sampling of 72 students. The data collection technique was carried out using 20 multiple-choice test instruments. The data analysis technique was carried out using descriptive analysis techniques and inferential analysis techniques. Main Findings: The results showed that classes that used the True or False learning strategy based on domino cards had higher average scores than classes that did not use the strategy. Regression analysis indicated a significant influence of this learning strategy on the learning outcomes of class XI science students at Public High School 8 Bandar Lampung, with a calculated t value greater than the t table and a significance level of 0.05. Novelty/Originality of this study: The novelty of this research can lie in the innovative approach in using the